The new handbook of counseling supervision - Borders, Leslie DiAnne, 1950-; Brown, Lori L. (New York, NY : Routledge, 2022)
"The classic edition of this groundbreaking book includes a new preface from the authors discussing developments in the field since the handbook's publication. Chapters provide an overview of best principles and best practices in counseling supervision process, one that is firmly rooted in the recent explosion of empirical research in this field. Sponsored by the Association for Counselor Education and Supervision (ACES), the book is targeted primarily at master's-level practitioners who want practical, how-to applications of the research literature rather than a comprehensive review of the supervision literature. It's also a useful supplement for more academic texts used for doctoral-level instruction in counseling supervision"--
Previous edition: New handbook of counseling supervision. 2005.
Keywords: Counseling -- Supervision of; PSYCHOLOGY / Psychotherapy / Counseling; EDUCATION / Counseling / General